Irrigation management for crop diversification in Sri Lanka: a synthesis in current research - Panabokke, Christopher R. (International Irrigation Management Institute, 1989)
The need to understand the technical and socioeconomic constraints in irrigation management for diversified cropping underlies this study. The main constraints identified include the unreliability and inequality of supply at the secondary and tertiary levels of the irrigation system, the lack of organization and management for sharing water below the secondary level, and the poor communication between agency staff and farmers in water delivery scheduling. Intervention studies have shown that flow measurements combined with regularly scheduled rotations and regular meetings between agency staff and farmers can enhance the management capacity of both. Because of the greater economic risks faced by farmers in growing non-rice crops as compared to rice, an assured market and a competitive price are indispensable for promoting diversified cropping.